GE_GERICHTE P/15550/2022 vom 9. Juni 2023 - GE Cour de justice (2023)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DROIT D'ÊTRE ENTENDU;PLAINTE PÉNALE;RENONCIATION(SENS GÉNÉRAL);LÉSION CORPORELLE | CPP.310; CP.30; CPP.382; CPP.120; CP.123; Cst.29.al2